Formulation and Evaluation of Anti-Bacterial Gel From Extracts of Butterfly Ash and Gold Bloom - Dhage Sejal,; Pandey Kavita R,; Baheti Jagdish R,; Chavhan Ketaki,; Shirbhate Trupti,; Sonkusare Rashmi, (Asian Journal of Pharmaceutical Research and Development, 2025)
The main objective of the current research study is to formulate and evaluate a topical herbal gel containing Bauhinia variegata Linn and Tagetes erecta Linn flower extracts for their anti-microbial activity against the most common pathogen Staphylococcus aureus.S. aureus is most common pathogen affecting different organs of the human body and is responsible for mortalities. Flowers of Butterfly ash (Bauhinia variegata Linn) are traditionally used as blood cleaners, and laxatives and possess antimicrobial and wound-healing properties. Gold bloom (Tagetes erecta Linn) is an ornamental flowering plant. Its flower is used to treat liver problems, scabies, fever and epileptic convulsions, and skin toner. They are also known for their astringent, carminative, and stomachic properties. It is also found to be useful against microbial infections and has wound-healing properties. A total of three herbal gel formulations were prepared using 1.0% of gelling agents carbopol 934 (G1—G-3) and the formulated gels were evaluated for physical appearance, viscosity, pH, spreadability, washability, primary skin irritation tests, and antimicrobial activity by agar well diffusion technique using azithromycin as a standard. No erythema or edema was observed in the skin irritation test confirming the gel to be nontoxic and safe. An attempt has been made to formulate and evaluate a new herbal combination to treat microbial infection. Formulation G2 was found to be superior among the three formulations as it rendered very good antimicrobial activity and was found to be better in other parameters.